A chemical screen for modulators of mRNA translation identifies a distinct mechanism of toxicity for sphingosine kinase inhibitors. - Alba Corman; Dimitris C Kanellis; Patrycja Michalska; Maria Häggblad; Vanesa Lafarga; Jiri Bartek; Jordi Carreras-Puigvert; Oscar Fernandez-Capetillo (PLoS Biology, 2021)
We here conducted an image-based chemical screen to evaluate how medically approved drugs, as well as drugs that are currently under development, influence overall translation levels. None of the compounds up-regulated translation, which could be due to the screen being performed in cancer cells grown in full media where translation is already present at very high levels. Regarding translation down-regulators, and consistent with current knowledge, inhibitors of the mechanistic target of rapamycin (mTOR) signaling pathway were the most represented class. In addition, we identified that inhibitors of sphingosine kinases (SPHKs) also reduce mRNA translation levels independently of mTOR. Mechanistically, this is explained by an effect of the compounds on the membranes of the endoplasmic reticulum (ER), which activates the integrated stress response (ISR) and contributes to the toxicity of SPHK inhibitors. Surprisingly, the toxicity and activation of the ISR triggered by 2 independent SPHK inhibitors, SKI-II and ABC294640, the latter in clinical trials, are also observed in cells lacking SPHK1 and SPHK2. In summary, our study provides a useful resource on the effects of medically used drugs on translation, identified compounds capable of reducing translation independently of mTOR and has revealed that the cytotoxic properties of SPHK inhibitors being developed as anticancer agents are independent of SPHKs.